ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI RETURN SAHAM (Studi Empiris pada Perusahaan Manufaktur Sektor Makanan dan Minuman di Bursa Efek Indonesia Periode 2018-2021) - Nova Anggya Prestiana; Agus Endro Suwarno (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to analyze Factors Affecting Stock Returns (Empirical Study on Manufacturing Companies in the Food and Beverage Sector on the Indonesia Stock Exchange 2018-2021 Period). The data used are secondary data obtained from the publication of the Indonesia Stock Exchange (IDX) website and the official website of each company. The analytical tool used in this study is multiple linear regression analysis (Multiple Linear Regression), by applying classical assumption testing and hypothesis testing. The results of this study indicate that partially, only the accounting profit has a positive and significant effect on stock returns. While the operating cash flow and return on equity have no significant effect on stock returns. Simultaneously, accounting profit, operating cash flow, and return on equity have a significant effect on stock returns.